Scaling relative incentive value in consummatory behavior - Papini, Mauricio Roberto (2006)
Surprising downshifts from more preferred (training incentive) to less preferred incentives (test incentive) are usually accompanied by emotional activation and suppression of conditioned behavior in rats. Two experiments were designed to determine whether consummatory behavior is similarly affected by downshifts of equal proportions. Within limits, the degree of consummatory responding during incentive downshift was similar with equal ratios of test concentration to training concentration. Thus, 32% to 4% and 16% to 2% downshifts (1:8 test/training ratios) caused similar levels of consummatory behavior, despite differences in the absolute concentrations of the solutions involved in the downshift. An interpretation based on sensory contrast was discarded because of the long intervals between training and test solutions (40 min and 24 h in Experiments 1 and 2, respectively). It is suggested that Weber’s law regulates behavioral suppression after reward downshifts. A theoretical framework for the interpretation of these data is presented.